Autologous Stem-Cell-Based Gene Therapy for Inherited Disorders: State of the Art and Perspectives - Staal, Frank J. T.; Aiuti, Alessandro; Cavazzana, Marina (Frontiers in Pediatrics, 2019)
Gene therapy using patient's own stem cells is rapidly becoming an alternative to allogeneic stem cell transplantation, especially when suitably compatible donors cannot be found. The advent of efficient virus-based methods for delivering therapeutic genes has enabled the development of genetic medicines for inherited disorders of the immune system, hemoglobinopathies, and a number of devastating metabolic diseases. Here, we briefly review the state of the art in the field, including gene editing approaches. A growing number of pediatric diseases can be successfully cured by hematopoietic stem-cell-based gene therapy.